Confronting Autism in Urban Bangladesh: Unpacking Infrastructural and Cultural Challenges - Ehsan, Upol; Sakib, Nazmus; Haque, Md Munirul; Soron, Tanjir; Saxena, Devansh; Iqbal Ahamed, Sheikh; Schwichtenberg, Amy; Rabbani, Golam; Akter, Shaheen; Alam, Faruq; Begum, Azima; Ahmed, Syed Ishtiaque (EAI Endorsed Transactions on Pervasive Health and Technology, 2018)
Autism Spectrum Disorder (ASD) is a critical problem worldwide; however, low and middle-income countries (LMICs) often suffer more from it due to the lack of contextual research and effective care infrastructure. Moreover, ASD in LMICs offers unique challenges as cultural misperceptions and social practices often impede effective care there. However, the recent growth in mobile phone adoption in many LMICs has created a timely opportunity for improving ASD care practices through digital means. We present qualitative findings on the challenges of designing mobile assistive technologies for ASD in Bangladesh. Our data reveals a set of technical, social, and cultural challenges with caregivers and care professionals for designing a meaningful technology for them. We show how those challenges are deeply rooted in the broader infrastructural and cultural tensions of the country. We also present embedded design implications to overcome these challenges.